Unraveling the complex role of tumor-associated neutrophils within solid tumors - Yingxin Wang; Jiakang Ma; Yuhao Liu; Weiheng Cui; Xiaodong Chu; Yusheng Lin; Lu Wang (Cancer Immunology, Immunotherapy)
Abstract Neutrophils are integral to the frontline defense against pathogenic bacterial and fungal invasions. Beyond their traditional roles, these cells are increasingly recognized for their dualistic contributions to the pathology of autoimmune and inflammatory diseases, as well as their complex involvement in cancer progression. Neutrophils interact with different disease states, highlighting their potential as therapeutic targets. Within tumor microenvironment (TME), tumor-associated neutrophils (TANs) exhibit a functional dichotomy, capable of either fostering or impeding tumor growth and metastasis. This binary functional potential of TANs, under certain conditions, suggests a reversible state that could transition from tumor-promoting to tumor-eradicating phenotypes. Despite the critical implications of such functional plasticity, systematic studies of TAN behavioral shifts in the context of cancer immunotherapy remain scarce. Herein, we review recent advancements in the understanding of TANs within the TME, highlighting their binary regulatory effects on solid tumors. Leveraging the latest insights from experimental and clinical research, this review elucidates the complex roles of TANs in tumor development and explores their molecular interactions as potential therapeutic targets. The elucidation of these mechanisms holds promise for novel cancer treatment strategies, aiming to improve patient outcomes by manipulating the tumor-promoting or -suppressing functions of TANs.